Integrasi Self-Regulated Learning dan Motivasi Intrinsik: Fondasi Prestasi Akademik Mahasiswa - Ningsih, Dewi Puspita; Anggraini, Erna (MANDALA WIDYA: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the relationship between Self-Regulated Learning (SRL) and intrinsic motivation in relation to students’ academic achievement, emphasizing the importance of integrating both constructs to foster autonomous learning in higher education.The literature indicates that SRL functions as a strategic mechanism that enables students to plan, monitor, and evaluate their learning processes, while intrinsic motivation serves as a psychological driver that sustains persistence and engagement in academic activities. Theoretical and empirical syntheses affirm that SRL and intrinsic motivation do not operate in isolation but rather complement each other in promoting optimal academic performance. Their integration has been shown to reduce maladaptive behaviors such as procrastination, lower academic stress, and enhance self-efficacy and the quality of students' learning strategies. Nevertheless, previous studies still face limitations, particularly the lack of research exploring the integration of SRL and intrinsic motivation within digital learning environments, as well as a shortage of interdisciplinary approaches. Therefore, future research should focus on exploring the interaction between these variables using more diverse methodological approaches, including interventions grounded in motivational theory. The practical implications of this study highlight the need for higher education learning strategies that promote active engagement, provide autonomy, and strengthen self-regulation skills. In this regard, reinforcing SRL and intrinsic motivation is not only essential for academic success but also for cultivating lifelong, independent, and adaptive learners.